2002
DOI: 10.1093/jnen/61.8.710
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-β Counteracts Inflammatory Mediator-Induced Effects on Brain Endothelial Cell Tight Junction Molecules—Implications for Multiple Sclerosis

Abstract: To elucidate mechanisms of endothelial cell (EC) dysfunction in CNS inflammatory responses and beneficial effects of interferon-beta (IFN-gamma) in multiple sclerosis (MS), we analyzed effects of individual and combinations of soluble inflammatory mediators on the intracellular localization of the EC tight junction-associated molecules zonula occludens-1 and -2 (ZO-1 and ZO-2) in human brain ECs. The cytoplasm in the majority of cells in control EC cultures was clear; ZO-1 and ZO-2 were localized peripherally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 72 publications
1
21
0
Order By: Relevance
“…Enhanced barrier properties induced by IFN activity could potentially protect the endothelium from external permeabilizing factors through resistance to their down regulation (38,45). In the present study, TNF-a-mediated permeability was partially inhibited at the early DENV infection phase (Fig.…”
Section: Discussionsupporting
confidence: 48%
“…Enhanced barrier properties induced by IFN activity could potentially protect the endothelium from external permeabilizing factors through resistance to their down regulation (38,45). In the present study, TNF-a-mediated permeability was partially inhibited at the early DENV infection phase (Fig.…”
Section: Discussionsupporting
confidence: 48%
“…16 Moreover, application of toxic concentrations of H 2 O 2 resulted in an obvious redistribution of ZO-1 and ZO-2 as well as in distinct changes of cell morphology in a human brain endothelial cell line. 41 The authors stated that the changes they observed in vitro were very sim- ilar to changes they found in active MS lesions with an intracellular staining for ZO-1 and ZO-2. These data point toward a functional relevance of the immunolocalization patterns of TJ-associated proteins in BBB endothelium.…”
Section: Fig 4 Dose-dependent Stabilization Of the In Vitro Blood-brmentioning
confidence: 78%
“…IFN-I has been shown to stabilize the permeability of the blood brain barrier and to block disintegration of the endothelial barrier induced by proinflammatory mediators, such as IFNγ, TNFα and histamine [46][48]. Also, TLR9-triggered protection against experimental colitis, which reflects bacterial invasion, was IFN-I dependent [49], and poly(I:C), a strong IFN-I inducer, protected mice against inflammatory bowel disease [50].…”
Section: Discussionmentioning
confidence: 99%